Evaluation of Occupational Health and Safety at the Sterilizer Station with the HIRARC Method at PT. Beurata Subur Persada - Fachrul Razi; Arie Saputra (Jurnal Inotera, 2023)
PT. Beurata Subur Peusada is a factory engaged in the palm oil processing industry (PMKS). PT. Beurata Subur Persada is in the area of Babah Dua Village, Tadu Raya District, Nagan Raya Regency. Based on the company's historical data during the 2019-2022 period there have been 5 cases of accidents at the PT. Beurata Subur Peusada. The purpose of this research is to condition a significant level of work accident rates at the sterilizer station. The method used is Hazard Identification Risk Assessment and Risk Control (HIRARC). The results of the risk assessment of the PT. The potentially dangerous Beurata Subur Peusada consists of 25% extreme risk, 50% medium risk, and 25% high risk, and 0% low risk. Control measures that can be taken are to provide instructions to workers to work according to company SOPs and always use PPE, conduct training or seminars for workers in which there are recommendations for using PPE and always work according to SOPs and tighten regulations.